Yiqi Huoxue Recipe Delayed Intervertebral Disc Degeneration by Activating Autophagy - Dai, Feng; Yu, Pengfei; Yu, Zhenhan; Jiang, Hong; Ma, Zhijia; Liu, Jintao (Frontiers in Pharmacology, 2021)
Autophagy has been proved to occur in rats with intervertebral disc degeneration (IVDD). Yiqi Huoxue recipe (YQHXR), an effective therapy of traditional Chinese medicine, was widely used for ruptured lumbar disc herniation under clinical observation. More importantly, YQHXR positively regulated the expression of autophagy-related proteins. However, little is known about the significance of YQHXR in the pathologic process of IVDD. Therefore, this study explored the protective effect of YQHXR based on IVDD rat model through magnetic resonance imaging and histopathologic analysis. Then we evaluated the formation of autophagosomes in the degenerated intervertebral disc by transmission electron microscope. Real-time PCR was used to detect the changes of autophagy-related genes. Western blot and immunoprecipitation were used to assess the protein expression of the autophagy-related pathway. We found that YQHXR-induced autophagy attenuated the release of inflammatory factors. In addition, YQHXR promoted the formation of Beclin1-VPS34 complex to activate autophagy through not only activation of the upstream protein AMPK and upregulation of the deubiquitinase USP13, thus in turn alleviating the development of IVDD. We proposed the potential molecular mechanism of YQHXR on autophagy for the first time, so as to provide a theoretical and experimental basis for the clinical application of YQHXR in the treatment of IVDD-related diseases.